Experiences of Persons with Disabilities in Starting and Maintaining Sexual Relationship in African Universities - Ephraim Lemmy Nuwagaba (Indonesian Journal of Disability Studies, 2018)
Despite discrimination, isolation and marginalization, many African University students with disabilities engage in sexual relationships. Some of these relationships involve only those with disability and others are between those with and those without disability. This paper discusses the opportunities, experiences, challenges and strategies that University students with hearing, physical and visual disabilities have to start and maintain sexual relationships at Kyambogo University, Uganda. Results show that their sexual behaviours are shaped by their perceptions, the environment and African culture and traditions rooted in African Ubuntu philosophy. The conclusion is that the university provided opportunities and challenges to their sexual relationships and that those with positive attitudes enjoy healthy sexual relationships and were also better able to deal with relationship pressures that might negatively affect their relationships.